PENGARUH MEDIA ULAR TANGGA BERBANTUAN QR CODE CANVA EDU TERHADAP PEMAHAMAN BANGUN DATAR SISWA KELAS III SEKOLAH DASAR - Dera Wibowo, Anggun; Susiloningsih, Wahyu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using a snakes and ladders game media assisted by QR Code Canva Edu on third-grade elementary school students’ understanding of plane geometry concepts. The background of this study is based on students’ low level of understanding of plane geometry material due to the learning process being conducted in a one-way manner, with teachers delivering material primarily through printed learning resources such as textbooks and student worksheets as the main references. The snakes and ladders game media is a board game-based learning tool designed with squares containing learning materials and activities to help students understand plane geometry concepts in a concrete and enjoyable way. The integration of QR Codes in the snakes and ladders media functions to provide access to interactive digital content, such as animated instructional videos, thereby enriching the learning experience and increasing student engagement. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The research subjects were third-grade students of SDN Kepuhkiriman 1, consisting of 50 students, with 25 students in the experimental group and 25 students in the control group. Data were collected using pretest and posttest instruments that had been tested for validity and reliability. Data analysis was conducted using normality testing, homogeneity testing, and hypothesis testing through an independent samples t-test. The results of the study indicate that there is a difference between the posttest scores of the experimental group and the control group. Therefore, it can be concluded that the use of snakes and ladders game media assisted by QR Code Canva Edu has a significant effect on third-grade elementary school students’ understanding of plane geometry concepts.